Fat deposition of broiler chickens fed a high-fat diet contained Sauropus androgynus leaf extract plus turmeric powder - Kususiyah, K.; Santoso, U.; Fenita, Y.; Putranto, A. M. H.; Suharyanto, S. (Diponegoro University, 2019)
A factorial design was used to analyzethe influenceofSauropus androgynusleaf extract (SALE) and turmeric powder (TP) on fat deposition in broilers fed high-fat diet. The first factor was the source of fat (6% beef fat and 6% palm oil), and the second factor was SALE plus TP [0 g SALE plus 0 g TP (G1), 9 g SALE plus 0.5 g TP (G2), 18 g SALE plus 0.5 g TP (G3), 9 g SALE plus 1 g TP (G4), 18 g SALE plus 1 g TP (G5)]. SALE plus TP affected cholesterol,lauric acid, myristic acid, palmitic acid, stearic acid and eicosapentaenoic acid contents (p<0.01).Fat sources affected fat, cholesterol, lauric acid, myristic acid, palmitic acid, stearic acid and eicosapentaenoic acid (p<0.01). There was a significant interaction between the two factorson fat, cholesterol, lauric acid, palmitic acid, stearic acid, and eicosapentaenoic acid contents. In conclusion, 18 g SALE plus 1 g TP supplementation to high-fat diet resulted in lower stearic acid, but it resulted in higher eicosapentaenoic acid. Supplementation of SALEplus TPto a high-fat diet lowered cholesterol content and changed fatty acidscomposition.